Community-based care for autistic youth: community providers’ reported use of treatment practices in the United States - Drahota, Amy; Sridhar, Aksheya; Moskowitz, Lauren J.; Kerns, Connor M.; Soorya, Latha; Wainer, Allison; Cohn, Elizabeth; Lerner, Matthew D. (Frontiers in Psychiatry, 2023)
To illustrate the landscape of community-based care for autistic youth in the United States, we identified transdisciplinary psychosocial intervention practice sets that community providers report utilizing to care for this population, and examined characteristics associated with providerreported utilization. The Usual Care for Autism Study (UCAS) Survey assessed provider demographics and provider-reported use of transdisciplinary practices for common ASD cooccurring problems: social difficulties, externalizing behaviors, and anxiety. Community practitioners (N=701) from allied health, behavioral, education, medical, mental health and other disciplines who treat or work with autistic youth (7-22 years) participated. Exploratory factor analysis yielded four factors: Consequence-Based Strategies (CBS), Cognitive-Behavioral and Therapy Strategies (CBTS), Antecedent-Based Strategies (ABS), and Teaching Strategies (TS). Providers across disciplines reported utilizing ABS more often than other sets. Providers from behavioral disciplines, with less than 4-year or Master degrees, or with more experience reported the most use of ABS, CBS and CBTS. Medical and behavioral providers reported the most use of TS. Setting and child characteristics were associated with practice set use, indicating variability by disability and client socioeconomic status. Findings reflect the complexity and inconsistency of the service landscape for autistic youth across the U.S. Only by understanding the service landscape and predictors of practice utilization, can researchers, policymakers, provider groups, and the autistic community facilitate effective implementation strategy development and use to ultimately improve community-based care.